Determination the Critical Component Machine using AHP Method for Reliability Centered Maintenance - Shofi Fitrotis Salimah (International Journal of Science, Engineering, and Information Technology, 2023)
Identification of critical components is one of the important steps in reliability-centered maintenance. This paper aims to develop a strategy to integrate key factors related to maintenance with component/sub system criticality. To analyze the criticality of a component, five criteria are used, namely duration of maintenance, probability of failure, level of risk of production process disruption due to component failure, facilities required for repair, and maintenance costs. A hierarchical network is created to identify important components based on these criteria. The Analytical Hierarchy process is one method to facilitate maintenance managers in making decisions in prioritizing maintenance of various components/failure modes so that the maintenance system runs more effectively and efficiently. Theoretical principles and real cases from an industry are analyzed to explain the implications of the proposed method. The results of the study provide a realistic solution in determining the priority of critical components in a reliability-centered maintenance plan. Article History Received 00 December 00Received in revised form 00 January 00Accepted 00 February 00